Physical modification of starches from cassava cultivars in Uganda f or food thickening - Madiesse, Diana F.L. (Kampala, 2015)
Unpublished dissertation (Msc. FST) - Makerere University, 2015
Includes bibliographical references.
Keywords: Cassava flour industry -- Uganda; Starch industry